(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence and characteristics of high-risk HPV infection among women attending Vinmec Times City International General Hospital. Research methods: A cross-sectional study was conducted on 381 women who underwent concurrent high-risk HPV DNA testing and cervical cytology screening at Vinmec Times City International General Hospital from August 2024 to March 2025. Results: The mean age of participants was 44.6 ± 12.5 years. The mean age at menarche and menopause were 11.7 ± 0.7 years and 49.9 ± 0.8 years, respectively. Nearly half of the participants (49.1%) had a history of gynecological disease treatment. The overall HPV prevalence was 13.6%. Among HPV-positive cases, HPV type 16 accounted for 7.7%, type 18 for 11.5%, other 12 high-risk types for 65.4%, and multiple infections for 15.4%. Women with cervical lesions were 2.1 times more likely to have high-risk HPV infection than those without lesions (OR = 2.1; 95% CI: 1.1-4.0; p < 0.05). Conclusion: The prevalence of high-risk HPV infection among women attending Vinmec Times City International General Hospital was 13.6%, with types 18, 16, and other high-risk genotypes predominating. HPV infection was significantly associated with cervical lesions, emphasizing the critical role of HPV in cervical pathology and the importance of routine screening and HPV vaccination for effective cervical cancer prevention.